TINGKAT KECEPATAN MAKAN ULAT YANG MEMAKAN DAUN MERSAWA (ANISOPTERA COSTATA KORTH) - A’imatul Khoiriah; Dina Naemah; Yusanto Nugroho (Universitas Lambung Mangkurat, 2020)
This study aims to measure the speed of eating mersawa leafworms in units of cm / hour. The benefit of this study is to observe the feeding speed and the level of damage caused by caterpillar pests on Mersawa leaves (Anisoptera costata Korth). Caterpillars are pests that attack many leaves, leaves that are often attacked by caterpillars usually leaves are still young. In this study using three leaf materials namely medium leaf young leaves (not old and not young), and old leaves. Caterpillar pests eat the leaves at certain times, such as when the environment is quiet and calm. The safety of this feeding speed is done to find out how much the caterpillar eats leaves, this data collection is done when the leaves have been eaten with caterpillars, in this study the caterpillars ate a lot of leaves at night and in the morning. As for the life phase of this caterpillar, the data is collected every day until it becomes a beetle. the speed of eating caterpillar cm / hour the average value obtained was 0.0472 cm / hour, for the average feeding capacity per day obtained was 0.0143cm / day. Caterpillars eat a lot of leaves at night, during the daytime caterpillars do not carry out any activities,Keywords: Mersawa. Speed Of Eating, Caterpillar